Leadership behavior and organizational climate as perceived by administrators and staff at the Stella Maris High School Hualien, East Taiwan - Chuang, John B. (Animo Repository, 1985)
This study determined the leadership behavior of the administrators and the school organizational climate as well as the relationship between these two variables at the Stella Maris High School of Hualien in East Taiwan as perceived by its administrators and staff during school year 1984-1985.Sub-problems of the study were as follows: 1. What is the leadership behavior of the school administrators as perceived by the administrators themselves and the staff? 2. What is the leadership style range and adaptability of the administrators as perceived by the administrators themselves? 3. What is the organizational climate of the school as perceived by the administrators and staff? 4. Is there a significant difference between the perceptions of the administrators and the staff with respect to the leadership behavior of the administrators and the organizational climate of the school? 5. Is there a significant correlation between the administrators' leadership behavior and the school organizational climate in the Stella Maris? 6. What recommendations can be proposed for improving the leadership behavior of the school administrators and the organizational climate of the school based on the findings of this study?